2005
DOI: 10.1111/j.1365-2036.2005.02457.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary prophylaxis of variceal bleeding in cirrhotics unable to take β‐blockers: a randomized trial of ligation

Abstract: Summary Aim : To compare endoscopic banding ligation vs. no treatment in cirrhotics with intolerance or contraindications to β‐blockers for prevention of first bleeding in portal hypertension. Methods : A sample size of 214 was planned with all sizes of varices. However, the trial was stopped due to increased bleeding in 52 patients in the ligation group. The baseline severity liver disease and endoscopic features were similar. Ligation group: 25 (M/F = 21/4, mean age: 60 ± 9.37 years); 27 not‐treated group: 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 35 publications
0
29
1
1
Order By: Relevance
“…Some differences between our study and those of Schepke et al and Triantos et al are: (1) our use of proton pump inhibitors until complete varix obliteration; (2) the increasing time between RBL sessions to reduce complications and increase ulcer healing-4 to 5 weeks in our study 1 versus 1 week in the Schepke et al study 3 and 2 weeks in the Triantos et al study 8 (at 4 to 5 weeks banding ulcers were rare in our study); and (3) standardizing RBL techniques and varix obliteration among investigators before initiation of the study, which was part of our trial 1,9 but was not discussed in the other two studies. 3,8 Third, there may be subgroup differences in response to these therapies. 1 Our study results are particularly relevant to nonalcoholic patients with cirrhosis but without prior variceal bleeding who are awaiting OLT and have high-risk varices.…”
contrasting
confidence: 49%
See 1 more Smart Citation
“…Some differences between our study and those of Schepke et al and Triantos et al are: (1) our use of proton pump inhibitors until complete varix obliteration; (2) the increasing time between RBL sessions to reduce complications and increase ulcer healing-4 to 5 weeks in our study 1 versus 1 week in the Schepke et al study 3 and 2 weeks in the Triantos et al study 8 (at 4 to 5 weeks banding ulcers were rare in our study); and (3) standardizing RBL techniques and varix obliteration among investigators before initiation of the study, which was part of our trial 1,9 but was not discussed in the other two studies. 3,8 Third, there may be subgroup differences in response to these therapies. 1 Our study results are particularly relevant to nonalcoholic patients with cirrhosis but without prior variceal bleeding who are awaiting OLT and have high-risk varices.…”
contrasting
confidence: 49%
“…Second, technical differences, study design, and luck may account for the lower complication rates with RBL in our trial 1 compared with others, 3,8 and these are important factors to understand. Some differences between our study and those of Schepke et al and Triantos et al are: (1) our use of proton pump inhibitors until complete varix obliteration; (2) the increasing time between RBL sessions to reduce complications and increase ulcer healing-4 to 5 weeks in our study 1 versus 1 week in the Schepke et al study 3 and 2 weeks in the Triantos et al study 8 (at 4 to 5 weeks banding ulcers were rare in our study); and (3) standardizing RBL techniques and varix obliteration among investigators before initiation of the study, which was part of our trial 1,9 but was not discussed in the other two studies.…”
Section: Outcomes Effectiveness Tolerability and Direct Costs Of Pmentioning
confidence: 99%
“…Gotoh et al [107] concluded that EVL was ineffective as a prophylactic therapy, because both recurrence of and bleeding from oesophageal varices during a 18-month follow-up period were observed more frequently in the EVL group than in the EIS group (recurrence 56 % vs 16 %, bleeding 20 % vs 0 %). EVL was proved to be no more effective than no treatment in preventing initial variceal bleeding [108]. Repeated EIS was preferable to combined therapy with EVL as a means of preventing the recurrence of esophageal varices [109].…”
Section: Antifibrotic Therapymentioning
confidence: 99%
“…Rapid and sustained control of variceal bleeding remains the principal imperative of endoscopic intervention [7]. Several important clinical considerations influence the prognosis in individual patients.…”
Section: Introductionmentioning
confidence: 99%